PEMBANGUNAN KAWASAN PERBATASAN INDONESIA DENGAN NEGARA MALAYSIA DI WILAYAH KECAMATAN BADAU KABUPATEN KAPUAS HULU - AGUS MULYANA,SH.A.21211035, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis researching the problems Indonesia Border Area Development In Malaysia In Sub Region Badau Kapuas Hulu. From the results of research using normative legal research methods can be concluded: 1. Government Policy in the Kapuas Hulu Development Plan, based on the provisions of Law Number 25, 2004 on National Development Planning System, which produces RPJPD Years 2005-2025, RKPD 2011-2015 and Kapuas Hulu budgeting. Prior to the formation of BNPP, BPP and BPP Provincial District as the implementation of Law Number 43, 2008 on Regional State President Jo Regulation Number 12, 2010 on the National Border Management, Border Area Development Planning Kapuas Hulu become an integral part of RPJPD, RPJMD and RKPD Kapuas Hulu. However, after the formation of BNPP, BPP and BPP Province Kapuas Hulu, border area development planning Kapuas Hulu on Priority Area (Locations Priority) Badau, Puring Kencana, Putusibau North, South Putusibau, Embaloh Hulu, and Trunk Lupar, switch to BNPP. 2. The presence of the Minister of Home Affairs Regulation Number 2, 2011 on Guidelines Establishment of Regional Border Management Agency, which regulates the powers, duties and functions of the Border Management Agency (BPP) BPP provincial and regency/city in Article 6 and Article 7, essentially a government takeover of authority Provincial and Regency / City Government as provided for in Article 11 and Article 12 of Law Number 43, 2008, which led to legal and technical issues in the implementation of border area development Kapuas Hulu aspect of applying the principle of deconcentration, desentraliasai and tasks. 3. Locations Priority Badau is an area that has a superior resource potential for development of local economic activity and encourage regional economic units. Badau strategic position in the border country that has direct access to the East Malaysian state Srawak a driving factor (push factor) for the economic development in the District and surrounding Badau, towards the realization of the border as the front porch Homeland. Further recommended that the Minister of Home Affairs Number 2, 2011 on Guidelines Establishment of Regional Border Management Agency, which regulates the powers, duties and functions of the Border Management Agency (BPP) BPP provincial and district / city to take over the authority of the Provincial Government and District/ City as provided in Article 6 and Article 7 of Law Number 43, 2008, to do a judicial review to the Supreme Court because it is against Article 11 and Article 12 of Law Number 43, 2008 on territory or